Image Analysis of Surface Porosity Mortar Containing Processed Spent Bleaching Earth - Beng, Wei Chong; Rokiah, Othman; Putra Jaya, Ramadhansyah; Doh, Shu Ing; Xiaofeng, Li; Mohd Haziman, Wan Ibrahim; Mohd Mustafa Al Bakri, Abdullah; Sandu, Andrei Victor; Płoszaj, Bartosz; Szmidla, Janusz; Stachowiak, Tomasz (MDPI AG, Basel, Switzerland, 2021)
Image analysis techniques are gaining popularity in the studies of civil engineering materials. However, the current established image analysis methods often require advanced machinery and strict image acquisition procedures which may be challenging in actual construction practices. In this study, we develop a simplified image analysis technique that uses images with only a digital camera and does not have a strict image acquisition regime. Mortar with 10%, 20%, 30%, and 40% pozzolanic material as cement replacement are prepared for the study. The properties of mortar are evaluated with flow table test, compressive strength test, water absorption test, and surface porosity based on the proposed image analysis technique. The experimental results show that mortar specimens with 20% processed spent bleaching earth (PSBE) achieve the highest 28-day compressive strength and lowest water absorption. The quantified image analysis results show accurate representation of mortar quality with 20% PSBE mortar having the lowest porosity. The regression analysis found strong correlations between all experimental data and the compressive strength. Hence, the developed technique is verified to be feasible as supplementary mortar properties for the study of mortar with pozzolanic material.